Excessive whole-body exposure to 28 GHz quasi-millimeter wave induces thermoregulation accompanied by a change in skin blood flow proportion in rats - Ijima, Etsuko; Kodera, Sachiko; Hirata, Akimasa; Hikage, Takashi; Matsumoto, Akiko; Ishitake, Tatsuya; Masuda, Hiroshi (Frontiers in Public Health, 2023)
Limited information is available on the biological effects of whole-body exposure to quasi-millimeter waves (qMMW). The aim of the present study was to determine the intensity of exposure to increase body temperature and investigate whether thermoregulation, including changes in skin blood flow, is induced in rats under whole-body exposure to qMMW. The backs of conscious rats were extensively exposed to 28 GHz qMMW at absorbed power densities of 0, 122, and 237 W/m 2 for 40 minutes. Temperature changes in three regions (dorsal and tail skin, and rectum) and blood flow in the dorsal and tail skin were measured simultaneously using fiber-optic probes. Intensity-dependent temperature increases were observed in the dorsal skin and the rectum. In addition, skin blood flow was altered in the tail but not in the dorsum, accompanied by an increase in rectal temperature and resulting in an increase in tail skin temperature. These findings suggest that whole-body exposure to qMMW drives thermoregulation to transport and dissipate heat generated on the exposed body surface. Despite the large differences in size and physiology between humans and rats, our findings may be helpful for discussing the operational health-effect thresholds in the standardization of international exposure guidelines.